Health self-assessment rule-based expert system / Wan Ahmad Mujib Wan Hamdy - Wan Hamdy, Wan Ahmad Mujib (2006)
In Malaysia, the level of health conscious is can be considered quite low and usually when diagnostician a health problem is usually done by the doctors. There is also other ways to do a self-diagnosis by reading a books, magazine or from Internet. Therefore new tools of diagnose is needed to solve the problem. The title for this project is Health Self-Assessment Rule-Based Expert System. The system is a Webbased system that can provide an online diagnosis through questionnaire for the users where much faster and easier than reading books or magazines. The system is not to replace the expertise of the doctors but it will be a new way of diagnosis. There are three objectives in the research to be fulfilled. The first objective is to do research and analyze facts on the health problems in Malaysia. The second objective is to produce set of rules based on the facts that been researched and analyzed. The last objective is to develop rule-based expert system where the system can perform forward chaining technique that can accept the input and produce the output for users. The main components of the rule-based which are the inference engine and the knowledge base are able to function and produce output. The rules that been created had been combine with scoring model called weighted average. The function of the scoring model is to calculate the percentage for the output. Even-though the expert system manage to meet the setting objectives, there are still limitation that can be found affect the system. The solution to overcome the limitation is by expanding the ability of the system. As suggested, the future expansion is to add up three components which are the developer interface, conflict resolution and uncertainty management.